Смертельная ночь: [роман] / Хизер Грэм ; [пер. с англ. К. А. Ересько] - Грэм Хизер (Центрполиграф, 2010)
Экземпляры: (20180412) / Инвентарный номер: 40246 / Цена: 165.00 / Сис.шифр: И / Авт.знак: Г 91 / ГРНТИ: 17 / ББК: 84(7Coe)